2020
DOI: 10.13057/asianjagric/g030204
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of diseases of rice (Oryza sativa) in Kutai Kartanegara, Indonesia

Abstract: Abstract. Sopialena, Sofian, Nurdiana J. 2019. Diversity of diseases of rice (Oryza sativa) in Kutai Kartanegara, Indonesia. Asian J Agric 3: 55-62. This research aimed to identify the diversity of diseases that are becoming the main threat to four paddy varieties in Kutai Kartanegara, Indonesia. Though similar studies have been conducted, to our knowledge, this research brings significant findings related to the diverse categories of plant diseases in the specific geographical area. The study was performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Species 373, the most virulent race, was discovered in two locations in the Maros Regencies. Race 001 is Indonesia's most dominant race [21]. The dominant blast pathogen race in an area can change due to changes in genetic composition, and the blast fungus has a high mutation rate [22].…”
Section: Discussionmentioning
confidence: 99%
“…Species 373, the most virulent race, was discovered in two locations in the Maros Regencies. Race 001 is Indonesia's most dominant race [21]. The dominant blast pathogen race in an area can change due to changes in genetic composition, and the blast fungus has a high mutation rate [22].…”
Section: Discussionmentioning
confidence: 99%
“…This report is the first report in West Nusa Tenggara that one of the causes of damage to rice plant tissue is the blast disease Pyricularia oryzae. Several previous research in Indonesia reported that the cause of blast disease in rice crops in Bali by Magnaporte oryzae (Sugiarta et al 2021), Pyricularia oryzae found in West Java, Lampung, South Sumatra, West Kalimantan, and Bali (Kadeawi et al 2021), and Pyricularia grisea found in East Kalimantan (Sopialena et al 2019).…”
Section: Discussionmentioning
confidence: 96%
“…The Central Statistics Agency (BPS) reported that total rice production in Indonesia was 54.42 million tons of milled dry grain (GKG) in 2021. This figure decreased by 233.91 thousand tons or 0.43 percent compared to 2020 rice production, which was 54.65 million tons of milled dry grain (Sopialena and Nurdiana, 2019). One of the factors that affect the lack of rice production is the presence of plant diseases.…”
Section: Introductionmentioning
confidence: 97%